Polarization-controlled metasurface for simultaneous holographic display and three-dimensional depth perception - Guo Shuhan; Shao Yifan; Zhan Junjie; Yu Jiaqi; Wang Yubo; Choudhury Pankaj K.; Hernandez-Figueroa Hugo E.; Ma Yungui (Nanophotonics)
Simultaneous optical display and depth perception are crucial in many intelligent technologies but are usually realized by separate bulky systems unfriendly to integration. Metasurfaces, artificial two-dimensional optical surfaces with strong light–matter interaction capabilities at deep subwavelength scales, offer a promising approach for manufacturing highly integrated optical devices performing various complex functions. In this work, we report a polarization-multiplexed metasurface that can functionally switch between holographic display and Dammann gratings. By tailoring the incidence polarization, the metasurface can display high-quality holographic images in the Fresnel region or project a uniform spot cloud nearly covering the entire 180° × 180° transmissive space. For the latter, a projection and three-dimensional (3D) reconstruction experiment is conducted to elaborate the potential in retrieving 3D complex spatial information. The current results provide a prominent way to manufacture lightweight and highly-integrated comprehensive imaging systems especially vital for cutting-edge intelligent visual technologies.